Differences between capillary and venous blood counts in children-A data mining approach - Becker, Mathias; Gscheidmeier, Thomas; Gross, Hans-Juergen; Cario, Holger; Wölfle, Joachim; Rauh, Manfred; Metzler, Markus; Zierk, Jakob (International Journal of Laboratory Hematology, 2022)
Background Capillary sampling of blood counts is a well-established alternative to venipuncture in paediatrics. However, the sampling method has to be considered when interpreting test results, as measurements differ. Ethical and practical considerations prevent simultaneous venous and capillary sample acquisition in comprehensive paediatric cohorts that span all ages for the purpose of a direct method comparison, resulting in uncertainty regarding the interpretation of capillary test results. Methods We applied a data mining method to calculate the differences between capillary and venous blood count analytes using laboratory data collected during patient care. We examined 486 401 blood counts performed between 2010 and 2017 in two German paediatric tertiary care centers in children from birth to 18 years analysed on SYSMEX XE-2100 and SYSMEX XE-5000 devices, and analysed the differences between capillary and venous test results in 15 218 paired samples performed within 24 h. Results We identified the mean systematic differences between capillary and venous (capillary-venous) test results for haemoglobin (+6.5 g/L), haematocrit (+2.38%), platelet count (-7.01 x 10(9)/l), red cell count (+0.18 x 10(12)/L), white cell count (-0.64 x 10(9)/L), mean corpuscular cell volume (+2.07 fl), mean corpuscular haemoglobin (+0.33 pg), mean corpuscular haemoglobin concentration (-4.4 g/L) and red cell distribution width (+0.40%). The effect of age on these mean deltas is negligible, while the levels of test results influence the difference between capillary and venous test results in most analytes. Conclusions Our results improve guidance regarding the interpretation of capillary test results for children of all ages and in both physiological and pathological ranges.
CRIS-Team WoS Importer:2022-05-13